A FAST AND SIMPLE NEW QUESTIONNAIRE TO HIGHLIGHT THE COGNITIVE IMPAIRMENT IN HYPERTENSIVES: THE ASSOCIATION WITH ARTERIAL STIFFNESS. (June 2018) - Nazzaro, P.; De Caro, M.F.; Nardecchia, A.; Moscatelli, F. Caradonna; Contini, M.; Schirosi, G.; De Benedittis, L.; Aceto, G.; Papagni, A.M.; Vitali, I.; Laselva, G.
Abstract : Objective: The critical incidence of cognitive impairment in hypertensives leads into the need to adopt tools easy to use and able to precociously discern the neuropsychological deficit. Aim of the study was to verify, in relatively well-treated hypertensive patients, the discriminative ability of a brief questionnaire to discern the quality and the grade of a mild cognitive impairment and their association with the preclinical vascular damage. Design and method: Following a pilot study performed in healthy and hypertensive subjects, an 18-item (NPI) questionnaire, with a good internal coherency (alpha:0.87) and graded answers (never-very often: 1–4), exploring diverse neuropsychological abilities ascribable to different cerebral cortical areas, was administered to 375 grade1–2 hypertensives treated with ACEi or ARBs as monotherapy. In the patients, subdivided in tertiles, in order of the total score for cognitive impairment (CIStot), 196 with lower (LCIS), 120 with intermediate (ICIS) and 59 with higher (HCIS), but with similar education, metabolic assessment, history and hypertensive state (BPoff and ABPM), the preclinical vascular damage, structural as carotid intima-media thickness (IMT) and functional, as carotid-femoral pulse wave velocity (PWVcf), was determined. Results: Results. The analysis showed significant characteristics. (m ± s.d.; *:p < .05, **:p < .01, ***:p < .001 vs LCIS; °:p < .05, °°:p < .01, °°°:p < .001 vs ICIS) Figure. No caption available. In particular, psychophysical attitude (NPI1), brief-term memory (NPI3, NPI7) and problem solving (NPI6, NPI10) deficits are impaired in HCIS hypertensives. Pearson analysis pointed out the association between PWV and brief-term memory (.649***), and problem solving (.618**), attentive-cognitive functions under the control of frontal cortical areas. Conclusions: The findings show that between relatively well-treated hypertensives, the mild impairment of attentive-executive capabilities are associate with the arterial stiffness, before the onset of a preclinical structural vascular damage, as IMT, and are detectable by a new rapid and easy-to-use screening tool.